Clostridium prolinivorans sp. nov., a thermophilic bacterium isolated from an anaerobic reactor degrading propionate. Issue 10 (14th October 2020) - Huang, Yan; Wei, Zhixian; Cong, Lulu; Qiu, Zhongwei; Chen, Rui; Deng, Yu; Zhang, Yinggang; Fan, Hui; Ma, Shichun
Abstract : An anaerobic, Gram-stain-positive, spore-forming bacterium, designated strain PYR-10 T, was isolated from a mesophilic methanogenic consortium. Cells were 0.7–1.2×6.0–6.3 µm, straight or slightly curved rods, with flagellar motility. Growth was observed in PYG (peptone-yeast glucose) medium at pH 5.5–8.0 (optimum, pH 6.5), 30–55 °C (45 °C) and in NaCl concentrations of 0–15 g l −1 (0 g l −1 ). Phylogenetic analysis based on the 16S rRNA gene sequence indicated that strain PYR-10 T belongs to the genus Clostridium . The strain showed 95.4, 93.7, 93.5 and 93.0 % 16S rRNA gene sequence similarity to Clostridium swellfunianum DSM 27788 T, Clostridium pascui DSM 10365 T, Clostridium pasteurianum DSM 525 T and Clostridium punense DSM 28650 T, respectively. The genomic DNA G+C content was 27.7 mol%. The major cellular fatty acids of strain PYR-10 T were iso-C15 : 0, C16 : 0, C16 : 0 DMA, anteiso-C15 : 0 and C14 : 0 . The main polar lipids were glycolipid, phosphoaminoglycolipid, diphosphatidylglycerol, phosphatidylglycerol, phospholipids, phosphatidylethanolamine and lipids. An unknown menaquinone was detected. 2, 6-Diaminopimelic acid was not detected. The whole-cell sugars contained ribose and lower amounts of glucose. Based on the results of phylogenetic, chemotaxonomic and phenotypic analyses, strain PYR-10 T represents a novel species of the genus Clostridium, for which the name Clostridium prolinivorans sp. nov. is proposed. The type strain is strain PYR-10 T (=JCM 33161 T =CCAM 531 T =CGMCC 1.5286 T ).